Economic Viability of Industrial Hemp Production in Turkey - Ceyhan, Vedat; Turkten, Hatice; Yildirim, Cagatay; Canan, Selime (Elsevier, 2022)
Recent developments in industrial hemp sector have resulted in several differentiations in production, marketing, logistic and consumption pattern of industrial hemp (Cannabis sativa L.). Therefore, the study examined the economic viability of industrial hemp production in Turkey. Research data were collected from industrial hemp producers by using structured questionnaire and from Ministry of Agriculture and Forestry and other stakeholders such as merchants, retailer, and e-marketing platform through semi structured interview. Efficiency measures generated by data envelopment analysis (DEA), strengths, weaknesses, opportunities, and threats (SWOT) analysis and profitability measures were used to explore economic viability of industrial hemp production. Research findings showed that hemp stalk production cost per kilogram of only hemp fiber growing and dual-purpose growing were US $0.29/kg and US $0.41/kg, respectively. Dual-purpose growing model had the highest net revenue per hectare. Industrial hemp had the competitive advantage over fiber flax (Linum usitatissimum L.), while reverse was the case for cotton fiber and seed production (Gossypium sp.). Based on the findings of efficiency analysis, the mean economic, allocative, and technical efficiencies were 0.77, 0.92, and 0.84, respectively. Productive efficiency level of dual-purpose growing was higher comparing with other growing models. Research findings also showed that farm level hemp production and processing hemp by modern technology was economically viable, while the viability of processing hemp by conventional technology was not profitable in Turkey. The results of SWOT analysis revealed that lacking data, problems related mechanism of hemp markets, hemp value chain, production, lacking research and development (R&D), and legislation problems were main issues in Turkey. The study suggests encouraging the R&D activities and investments in hemp breeding and genetics, and developing processing facility of hemp farms to produce fiber and seed-based product. Producing hemp with appropriate cropping system and increasing technical knowledge of hemp farmers, especially on sex determination may positively affect the economic viability of hemp production.
Canan, Selime/0000-0002-8041-3272
Keywords: Industrial Hemp; Productive Efficiency; Economic Viability; Turkey